Conductive adhesive and preparation method thereof, negative electrode material, negative electrode sheet, and battery

By using conductive adhesives prepared by a mixture of conductive polymers and thiophene-polystyrene sulfonic acid in lithium-ion batteries, and forming a three-dimensional crosslinking network through phytic acid bridge, the structural damage caused by volume expansion during charging and discharging of silicon-based anode materials is solved, and the cycle stability and capacity retention rate of the battery are significantly improved.

CN119736055APending Publication Date: 2025-04-01AMPREUS WUXI CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411944915.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the structural damage caused by volume expansion and contraction during charging and discharging of silicon-based anode materials leads to a sharp decline in battery capacity and a decrease in cycle life.

Method used

The conductive adhesive prepared by mixing and dispersing conductive polymer with thiophene-polystyrene sulfonic acid mixture, and a three-dimensional crosslinking network is formed by phytic acid bridge to improve the mechanical properties and electrical conductivity of the conductive adhesive.

Benefits of technology

The cycle stability and capacity retention rate of silicon-based lithium-ion batteries are significantly improved, mechanical stability is enhanced, and structural damage caused by volume expansion is alleviated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736055A_ABST
    Figure CN119736055A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode binder and a preparation method thereof, a negative electrode material, a negative electrode plate, and a battery, and belongs to the technical field of lithium ion batteries. The conductive binder of the invention is obtained by uniformly dispersing conductive polymer gel particles in a polythiophene-polystyrene sulfonic acid mixture, reacting, and obtaining; the conductive polymer gel particles are obtained by mixing a conductive polymer with a phytic acid solution, adding ammonium persulfate to mix, standing for reaction, and drying. The preparation method of the conductive binder of the invention is simple, suitable for large-scale production, and can be further mixed with silicon nanomaterials to prepare negative electrode slurry, simplifying the components and pulping process of the negative electrode slurry, and at the same time, phytic acid bridges the conductive polymer and thiophene substances to form a three-dimensional cross-linked network, thereby improving the mechanical properties of the conductive binder, solving the problem of poor mechanical strength of the existing binder and structural damage caused by volume shrinkage and expansion of the negative electrode material during charging and discharging, and improving the cycle performance and rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a conductive adhesive and a preparation method thereof, a negative electrode material, a negative electrode sheet, and a battery. Background Art

[0002] With the widespread application of lithium-ion batteries in electric vehicles, portable electronic devices and renewable energy storage, the demand for high-performance negative electrode materials is becoming more and more urgent. Traditional graphite negative electrodes face theoretical capacity limitations (372mAh / g), which has led researchers to turn to silicon-based negative electrodes with theoretical capacity of up to 4200mAh / g. However, silicon is a semiconductor material, and its intrinsic properties make it less conductive than graphite electrodes, and its rate performance is poor. At the same time, silicon undergoes significant volume expansion (up to 300%) during the charge and discharge process, causing the electrode material to break, pulverize, peel off, and even collapse the entire structure, causing a sharp decline in the capacity of lithium-ion batteries, which seriously affects their cycle life.

[0003] In order to meet the above challenges, the performance of the binder, as an important component of the electrode material, is crucial to the overall performance of the battery. Traditional binders such as styrene-butadiene rubber (SBR) can provide basic mechanical bonding, but their conductivity is poor and it is difficult to meet the conductivity and kinetic requirements of lithium-ion batteries in high-silicon systems for electrode materials. In addition, organic solvents are often required in the preparation process of traditional binders, which not only increases production costs, but also brings environmental pollution and safety hazards. Therefore, it is urgent to develop a new conductive binder that has both excellent conductivity and good mechanical stability to meet the rate requirements of silicon-based negative electrode materials and inhibit volume changes during the cycle. At the same time, environmental friendliness and simplicity of the preparation process must also be considered.

[0004] Poly (3,4-ethylenedioxythiophene) (PEDOT) is a widely used conductive polymer with good conductivity, chemical stability and mechanical flexibility, and is considered to be a potential conductive binder material. However, PEDOT still has some limitations when used in silicon-based anodes. For example, its mechanical strength may not be sufficient to cope with the volume expansion of silicon, and the synthesis of traditional PEDOT binders usually requires the use of organic polar solvents as dopants, which not only increases the process complexity, but also may bring environmental and safety issues.

[0005] How to provide a binder that is safe and has sufficient mechanical strength while being able to cope with the volume expansion of silicon-based negative electrode materials is an urgent problem to be solved in this field. Summary of the invention

[0006] In view of the deficiencies of the prior art, the present invention provides a conductive binder and a preparation method thereof, a negative electrode material, a negative electrode plate, and a battery. The present invention mixes and disperses a conductive polymer with a thiophene-polystyrene sulfonic acid mixture to obtain a conductive polymer-containing binder. The preparation method is simple and suitable for large-scale production. The conductive polymer can be further mixed with silicon nanomaterials to prepare negative electrode slurry, simplifying the components and slurrying process of the negative electrode slurry. At the same time, phytic acid bridges the conductive polymer and thiophene substances to form a three-dimensional cross-linked network, which improves the mechanical properties of the conductive binder and solves the problem of poor mechanical strength of the existing binder. At the same time, the three-dimensional continuous conductive network can provide more contact sites, form a more uniform electron diffusion path, significantly enhance mechanical stability, and effectively alleviate the structural damage caused by volume expansion and contraction of silicon-based negative electrode materials during charging and discharging, thereby significantly improving the cycle stability of silicon-based lithium-ion batteries.

[0007] The technical solution of the present invention is as follows:

[0008] The first aspect of the present invention protects a method for preparing a conductive adhesive, the preparation method comprising: uniformly dispersing conductive polymer gel particles in a polythiophene-polystyrene sulfonic acid mixture, reacting to obtain a polythiophene / conductive polymer composite, namely, a conductive adhesive;

[0009] The conductive polymer gel particles are obtained by mixing a conductive polymer with a phytic acid solution, adding ammonium persulfate, mixing, standing for reaction, and drying.

[0010] Preferably, the method for preparing the conductive polymer gel particles comprises the following steps:

[0011] S1: adding phytic acid solution to the conductive polymer and mixing them evenly to obtain a conductive polymer-phytic acid solution;

[0012] S2: dissolving ammonium persulfate in water to obtain an ammonium persulfate solution;

[0013] S3: cooling the conductive polymer-phytic acid solution and the ammonium persulfate solution, mixing them, standing them for reaction, filtering, washing, and drying them to obtain conductive polymer gel particles;

[0014] In S1, the molar ratio of the conductive polymer to the phytic acid is 1-5:0.24-1.2;

[0015] And / or, the mass concentration of the phytic acid solution is 20-50%;

[0016] In S2, the concentration of the ammonium persulfate solution is 0.25 mmol / mL-1.25 mmol / mL;

[0017] In S3, the molar ratio of the conductive polymer in the conductive polymer-phytic acid solution to the ammonium persulfate in the ammonium persulfate solution is 1-5:0.25-1.25;

[0018] And / or, the cooling temperature is 1-4°C;

[0019] And / or, the temperature of the static reaction is 1-4°C and the time is 8-24h.

[0020] Preferably, the conductive polymer includes at least one of polyaniline and polypyrrole;

[0021] And / or, the particle size of the conductive polymer gel particles is 60-100 nm;

[0022] and / or, the mass volume ratio of the conductive polymer gel particles to the polythiophene in the polythiophene-polystyrene sulfonic acid mixture is 6-14 mg / mL: 1-4;

[0023] And / or, the polythiophene comprises poly-3,4-ethylenedioxythiophene;

[0024] And / or, in the preparation of the polythiophene / conductive polymer composite, the reaction temperature is 60-90° C. and the reaction time is 8-16 hours.

[0025] The second aspect of the present invention protects a conductive adhesive prepared by the preparation method described in the first aspect, wherein the viscosity of the conductive adhesive is 1000-5000 mPa.s.

[0026] The third aspect of the present invention protects a negative electrode material, including a silicon nanomaterial, the conductive binder described in the second aspect, or the conductive binder prepared by the preparation method described in the first aspect.

[0027] Preferably, the particle size of the silicon nanomaterial is 60-100 nm;

[0028] And / or, in the negative electrode material, the mass ratio of the silicon nanomaterial to the conductive binder is 1-2:8-9;

[0029] And / or, the negative electrode material is obtained by mixing and stirring the silicon nanomaterial and the conductive binder.

[0030] The fourth aspect of the present invention protects a negative electrode plate, including a negative electrode current collector and a negative electrode material layer coated on at least one surface of the negative electrode current collector; the negative electrode material layer includes the negative electrode material described in the third aspect above.

[0031] Preferably, the thickness of the negative electrode material layer is 50-150 μm;

[0032] And / or, the coating amount of the negative electrode material is 1.5-2.0 mg / cm 2 .

[0033] Preferably, the preparation method of the negative electrode sheet is: coating the negative electrode material on at least one surface of a negative electrode current collector and drying the coating.

[0034] The fifth aspect of the present invention protects a battery, including a positive electrode plate, an electrolyte, and the negative electrode plate described in the fourth aspect.

[0035] The beneficial technical effects of the present invention are:

[0036] (1) The present invention uses phytic acid containing multiple phosphate groups and a conductive polymer to chemically synthesize and prepare conductive polymer gel particles. The conductive polymer gel particles not only have the properties of a conductive polymer but also introduce abundant hydroxyl groups in the phosphate groups of phytic acid. The conductive polymer gel particles are further physically mixed and reacted with polythiophene-polystyrene sulfonic acid to obtain a polythiophene / conductive polymer composite conductive adhesive having a three-dimensional continuous conductive network structure and more contact sites. The process is simple, easy to operate, and suitable for large-scale production.

[0037] (2) The polythiophene / conductive polymer composite conductive binder prepared by the present invention breaks through the limitation that most of the traditional polythiophene binder synthesis requires organic polar solvents as dopants. The phytic acid-doped polymer is used as a dopant, which avoids the environmental pollution and safety hazards that may be caused by the use of organic solvents. On the other hand, by means of phytic acid bridging polymers and polythiophene chains, the three-dimensional cross-linked network of polymers and the method of cross-linking polythiophene with high modulus polymers, the prepared polythiophene / polymer composite conductive binder is composed of a three-dimensional porous network formed by interconnecting polythiophene sheets embedded with polymer gel particles, which can greatly improve the mechanical stability of the polythiophene conductive binder. At the same time, the polythiophene / polymer composite conductive binder can provide a three-dimensional continuous conductive network, can provide more contact sites, form a more uniform electron diffusion path, significantly enhance the mechanical stability, and can effectively alleviate the structural damage caused by volume expansion and contraction of silicon-based negative electrode materials during charging and discharging, thereby significantly improving the cycle stability of silicon-based lithium-ion batteries.

[0038] (3) When the polythiophene / polymer composite conductive binder provided by the present invention is mixed with silicon nanoparticles as a negative electrode material for the preparation of negative electrode plates of silicon-based lithium-ion batteries, the phytic acid molecules in the polymer contain abundant hydroxyl functional groups, which form strong hydrogen bonds with the hydroxyl groups on the surface of the silicon nanoparticles, and can effectively inhibit the agglomeration of the silicon nanoparticles, making them easy to be evenly dispersed in the polythiophene / conductive polymer composite conductive binder system. Therefore, in the process of mixing and slurrying the phytic acid molecules with the silicon nanoparticles, there is no need to add additional dispersant, the preparation process is simple, and cost is saved.

[0039] (4) The silicon-based lithium-ion battery negative electrode sheet prepared by the polythiophene / conductive polymer composite binder provided by the present invention exhibits excellent electrochemical properties in batteries, especially button-type lithium-ion half cells, including high specific capacity, good rate performance and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a SEM photograph of the polyaniline gel particles prepared in Example 4 of the present invention.

[0041] Figure 2 These are SEM photos of the PEDOT / PANi conductive adhesive prepared in Example 4 of the present invention at different magnifications.

[0042] Figure 3 These are the cycle performance diagrams and rate performance diagrams of the silicon-based negative electrodes prepared with gel particles of different contents in Examples 1 and 4-5 of the present invention.

[0043] In the figure: a, rate performance diagram of gel particles with different contents; b, cycle performance diagram of gel particles with different contents.

[0044] Figure 4 The electrochemical performance diagrams of the batteries of Examples 4 and 6 of the present invention are shown.

[0045] In the figure: a, charge and discharge curve diagram of different active material mass ratios; b, cycle performance diagram of different active material mass ratios. DETAILED DESCRIPTION

[0046] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0047] The first aspect of the present invention provides a method for preparing a conductive adhesive, the preparation method comprising: uniformly dispersing conductive polymer gel particles in a polythiophene-polystyrene sulfonic acid mixture, reacting to obtain a polythiophene / conductive polymer composite, i.e., a conductive adhesive; the conductive polymer gel particles are obtained by mixing a conductive polymer with a phytic acid solution, adding ammonium persulfate to the mixture, allowing the mixture to react, and drying.

[0048] It can be understood that the conductive binder with a three-dimensional continuous conductive network prepared by the present invention has the function of both a conductive agent and an adhesive. On the one hand, it can maintain good contact between the active material and the current collector. On the other hand, the three-dimensional network structure of the conductive binder of the present invention is like a net with certain flexibility and rigidity, which plays a role of restraint and protection when the negative electrode material expands and contracts due to lithium insertion and extraction. The strong mechanical stress can reduce the material cracking and crushing caused by the volume change of silicon during the charge and discharge cycle, thereby improving the stability of the entire negative electrode during the cycle. The prepared battery cell has high specific capacity, good rate and long cycle life.

[0049] In some embodiments, the method for preparing the conductive polymer gel particles comprises the following steps:

[0050] S1: adding phytic acid solution to the conductive polymer and mixing them evenly to obtain a conductive polymer-phytic acid solution.

[0051] S2: Dissolve ammonium persulfate in water to obtain an ammonium persulfate solution.

[0052] S3: After cooling the conductive polymer-phytic acid solution and the ammonium persulfate solution, mix them, allow them to react, filter, wash, and dry them to obtain conductive polymer gel particles.

[0053] In some embodiments, in S1, the molar ratio of the conductive polymer to the phytic acid is 1-5:0.24-1.2, including but not limited to 1:0.24, 1:1.2, 5:0.24, 5:1.2, and 2:1.

[0054] In some embodiments, the mass concentration of the phytic acid solution is 20-50%, including but not limited to 20%, 30%, 40%, and 50%.

[0055] In some embodiments, in S2, the concentration of the ammonium persulfate solution is 0.25 mmol / mL-1.25 mmol / mL, including but not limited to 0.25 mmol / mL, 0.5 mmol / mL, 1.0 mmol / mL, and 1.25 mmol / mL.

[0056] In some embodiments, in S3, the molar ratio of the conductive polymer in the conductive polymer-phytic acid solution to the ammonium persulfate in the ammonium persulfate solution is 1-5:0.25-1.25, including but not limited to 1:0.25, 1:1.25, 5:0.25, 5:1.25, and 2:1.

[0057] In some embodiments, the cooling temperature is 1-4°C, including but not limited to 1°C, 2°C, 3°C, 4°C.

[0058] In some embodiments, the temperature of the static reaction is 1-4°C, including but not limited to 1°C, 2°C, 3°C, 4°C, and the time is 8-24h, including but not limited to 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h.

[0059] In some embodiments, the conductive polymer includes at least one of polyaniline and polypyrrole.

[0060] In some embodiments, the conductive polymer is preferably polyaniline.

[0061] In some embodiments, the preparation method of polyaniline gel particles is as follows: add a certain amount of aniline to an aqueous solution containing a certain amount of phytic acid, mix well, obtain solution A, and place it in a 4°C refrigerator to cool; dissolve a certain amount of ammonium persulfate in deionized water to obtain solution B, and place it in a 4°C refrigerator to cool. After solution A and solution B are cooled to 4°C, quickly mix the two, and gelation of the solution can be observed in a few minutes. Continue to place it in a 4°C refrigerator for 8 hours, wait for the polymerization reaction to be complete, filter, and wash with ethanol to remove by-products such as aniline oligomers and unreacted phytic acid. Dry at room temperature to obtain dark green PANi gel particle powder.

[0062] In some embodiments, the amount of aniline added is 1-5 mmol, including but not limited to 1 mmol, 2 mmol, 3 mmol, 4 mmol, and 5 mmol, the amount of phytic acid added is 0.24-1.2 mmol, including but not limited to 0.24 mmol, 0.5 mmol, 1.0 mmol, and 1.2 mmol, and the amount of ammonium persulfate added is 0.25-1.25 mmol, including but not limited to 0.25 mmol, 0.5 mmol, 1.0 mmol, and 1.25 mmol.

[0063] In some embodiments, the particle size of the conductive polymer gel particles is 60-100 nm.

[0064] In some embodiments, the mass volume ratio of the conductive polymer gel particles to the polythiophene in the polythiophene-polystyrene sulfonic acid mixture is 6-14:1-4, including but not limited to 6:1, 14:1, 6:4, 14:4, 8:3.

[0065] In some embodiments, the polythiophene includes poly-3,4-ethylenedioxythiophene.

[0066] In some embodiments, in the preparation of the polythiophene / conductive polymer composite, the reaction temperature is 60-90°C, including but not limited to 60°C, 70°C, 80°C, 90°C, and the reaction time is 8-16h, including but not limited to 8h, 10h, 12h, 14h, 16h.

[0067] The second aspect of the present invention provides a conductive adhesive prepared by the preparation method described in the first aspect, wherein the viscosity of the conductive adhesive is 1000-5000mPa.s, including but not limited to 1000mPa.s, 2000mPa.s, 3000mPa.s, 4000mPa.s, and 5000mPa.s.

[0068] It can be understood that the conductive binder prepared by the present invention avoids the introduction of solvents and has the properties of conductive polymers and binders, which simplifies the preparation process of negative electrode slurry, and the bonding degree can ensure its combination with the negative electrode and the bonding strength during charging and discharging. At the same time, by controlling the content of conductive polymers and adding phytic acid, the properties of conductive polymers are guaranteed, and a three-dimensional conductive network can be provided.

[0069] The third aspect of the present invention provides a negative electrode material, comprising a silicon nanomaterial, the conductive binder described in the second aspect, or the conductive binder prepared by the preparation method described in the first aspect.

[0070] In some embodiments, the particle size of the silicon nanomaterial is 60-100 nm, including but not limited to 60 nm, 70 nm, 80 nm, 90 nm, and 100 nm.

[0071] In the present invention, the particle size is measured by a laser particle size analyzer, and the viscosity is measured by a viscometer. The surface density is measured by cutting the prepared negative electrode sheet and the copper foil into small discs with a diameter of 4 cm and weighing them. The weight difference between the two is divided by the actual circular area to obtain the coating amount.

[0072] In some embodiments, in the negative electrode material, the mass ratio of the silicon nanomaterial to the conductive binder is 1-2:8-9, including but not limited to 1:8, 1:9, 2:8, 2:9.

[0073] In some embodiments, the negative electrode material is obtained by mixing and stirring the silicon nanomaterial and the conductive binder.

[0074] The fourth aspect of the present invention provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode material layer coated on at least one surface of the negative electrode current collector; the negative electrode material layer comprises the negative electrode material described in the third aspect above.

[0075] In some embodiments, the thickness of the negative electrode material layer is 50-150 μm, including but not limited to 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, and 150 μm.

[0076] In some embodiments, the coating amount of the negative electrode material is 1.5-2.0 mg / cm 2 , including but not limited to 1.5 mg / cm 2 、1.6mg / cm 2 , 1.7mg / cm 2 、1.8mg / cm 2 , 1.9mg / cm 2 , 2.0mg / cm 2 .

[0077] In some embodiments, the negative electrode sheet is prepared by coating the negative electrode material on at least one surface of a negative electrode current collector and drying the negative electrode material.

[0078] In some embodiments, the negative electrode sheet is prepared by coating the negative electrode material on two surfaces of a negative electrode current collector and drying the negative electrode material.

[0079] A fifth aspect of the present invention provides a battery, comprising a positive electrode plate, an electrolyte, and the negative electrode plate described in the fourth aspect.

[0080] It is understandable that the present invention does not limit the positive electrode plate, and any solution that can achieve the purpose of the present invention is within the protection scope of the present invention. Exemplarily, the positive electrode plate of the present invention is a lithium plate.

[0081] It is understandable that the present invention does not limit the electrolyte, and any solution that can achieve the purpose of the present invention is within the protection scope of the present invention. In some embodiments of the present invention, the electrolyte is 1M LiPF6 EC / DMC.

[0082] In some embodiments, the battery of the present invention further comprises a diaphragm. The present invention does not limit the diaphragm, and any diaphragm that can achieve the purpose of the present invention is within the protection scope of the present invention. Exemplarily, the diaphragm is a polypropylene diaphragm.

[0083] The present invention will be further described below in conjunction with embodiments and the like.

[0084] Example 1

[0085] The conductive adhesive is prepared as follows:

[0086] (1) Preparation of polyaniline (PANi)

[0087] 5 mmol of aniline was added to 2 mL of aqueous solution containing 1.2 mmol of phytic acid, and the mixture was mixed evenly to obtain solution A, which was then placed in a 4°C refrigerator for cooling; 1.25 mmol of ammonium persulfate was dissolved in 1 mL of deionized water to obtain solution B, which was then placed in a 4°C refrigerator for cooling.

[0088] After solution A and solution B are cooled to 4°C, they are quickly mixed and gelation of the solution can be observed in a few minutes. They are placed in a 4°C refrigerator for 8 hours. After the polymerization reaction is complete, they are filtered and washed with ethanol to remove byproducts such as aniline oligomers and unreacted phytic acid. After drying at room temperature, dark green PANi gel particle powder with a particle size of 60-100nm is obtained.

[0089] (2) Preparation of poly (3,4-ethylenedioxythiophene)-polyaniline (PEDOT / PANi) conductive adhesive

[0090] 5 mg of PANi gel particles were evenly dispersed in 3 mL of poly (3,4-ethylenedioxythiophene) PEDOT-polystyrene sulfonate PSS solution (purchased from Sigma-Aldrich, solid content 1.1%), and reacted at 90° C. for 10 h to obtain adhesive PEDOT / PANi.

[0091] A silicon-based lithium-ion battery negative electrode plate, the preparation method of which is as follows:

[0092] The obtained PEDOT / PANi conductive binder and silicon nanoparticles were mixed in a ratio of 1:9 using a magnetic stirrer for 2 hours to ensure that the silicon nanoparticles and the conductive binder were fully mixed; a clean copper foil (15mm×15mm) was taken and the prepared silicon slurry was evenly coated on the copper foil with a thickness of about 65μm; the coated copper foil was placed in an oven and dried at 120°C for 2 hours to remove moisture and solidify the slurry on the copper foil to obtain a silicon-based negative electrode. Among them, the average particle size of the silicon nanoparticles is 80nm, and the coating amount of the negative electrode material layer is 1.75mg / cm 2 .

[0093] A button-type lithium-ion half-cell, the assembly method of which is as follows:

[0094] In a glove box, the silicon-based negative electrode sheet, lithium metal sheet and polypropylene separator were stacked to ensure the isolation of the two electrodes. 1M LiPF6 EC / DMC electrolyte (300 μL) was injected and packaged into a button cell under vacuum conditions.

[0095] Example 2

[0096] The conductive adhesive is prepared as follows:

[0097] (1) Preparation of polyaniline (PANi)

[0098] 1 mmol of aniline was added to 2 mL of aqueous solution containing 1.2 mmol of phytic acid, and the mixture was evenly mixed to obtain solution A, which was then placed in a refrigerator at 2°C for cooling. 1.0 mmol of ammonium persulfate was dissolved in 1 mL of deionized water to obtain solution B, which was then placed in a refrigerator at 2°C for cooling.

[0099] After solution A and solution B are cooled to 2°C, they are quickly mixed and gelation of the solution can be observed in a few minutes. They are placed in a 2°C refrigerator for 10 hours. After the polymerization reaction is complete, they are filtered and washed with ethanol to remove byproducts such as aniline oligomers and unreacted phytic acid. Dark green PANi gel particle powder is obtained by drying at room temperature with a particle size of 60-100nm.

[0100] (2) Preparation of poly (3,4-ethylenedioxythiophene)-polyaniline (PEDOT / PANi) conductive adhesive

[0101] 6 mg of PANi gel particles were evenly dispersed in 1 mL of PEDOT:PSS solution and reacted at 60°C for 8 h to obtain adhesive PEDOT / PANi.

[0102] A silicon-based lithium-ion battery negative electrode plate, the preparation method of which is as follows:

[0103] The obtained PEDOT / PANi conductive binder and silicon nanoparticles were mixed in a ratio of 1:9 using a magnetic stirrer for 2 hours to ensure that the silicon nanoparticles and the conductive binder were fully mixed; a clean copper foil (15mm×15mm) was taken and the prepared silicon slurry was evenly coated on the copper foil with a thickness of about 50μm; the coated copper foil was placed in an oven and dried at 120°C for 2 hours to remove moisture and solidify the slurry on the copper foil to obtain a silicon-based negative electrode. Among them, the average particle size of the silicon nanoparticles is 80nm, and the coating amount of the negative electrode material layer is 1.6mg / cm 2 .

[0104] A button-type lithium-ion half-cell, the assembly method of which is as follows:

[0105] In a glove box, the silicon-based negative electrode sheet, lithium metal sheet and polypropylene separator were stacked to ensure the isolation of the two electrodes. 1M LiPF6 EC / DMC electrolyte (300 μL) was injected and packaged into a button cell under vacuum conditions.

[0106] Example 3

[0107] The conductive adhesive is prepared as follows:

[0108] (1) Preparation of polypyrrole

[0109] 4 mmol pyrrole was added into 2 mL aqueous solution containing 1.2 mmol phytic acid, and the mixture was evenly mixed to obtain solution A, which was then placed in a refrigerator at 1°C for cooling; 0.25 mmol ammonium persulfate was dissolved into 1 mL deionized water to obtain solution B, which was then placed in a refrigerator at 1°C for cooling.

[0110] After solution A and solution B are cooled to 1°C, they are quickly mixed and gelation of the solution can be observed in a few minutes. They are placed in a refrigerator at 1°C for 24 hours. After the polymerization reaction is complete, the solution is filtered and washed with ethanol to remove byproducts such as pyrrole oligomers and unreacted phytic acid. The solution is dried at room temperature to obtain a dark green polypyrrole gel particle powder with a particle size of 60-100 nm.

[0111] (2) Preparation of poly (3,4-ethylenedioxythiophene)-polypyrrole conductive adhesive

[0112] 14 mg of polypyrrole gel particles were uniformly dispersed in 3 mL of poly (3,4-ethylenedioxythiophene)-PSS solution, and the mixture was reacted at 80° C. for 16 h to obtain a viscous poly (3,4-ethylenedioxythiophene)-polypyrrole conductive adhesive.

[0113] A silicon-based lithium-ion battery negative electrode plate, the preparation method of which is as follows:

[0114] The obtained poly (3,4-ethylenedioxythiophene)-polypyrrole conductive binder and silicon nanoparticles were mixed in a ratio of 1:9 using a magnetic stirrer for 2 hours to ensure that the silicon nanoparticles and the conductive binder were fully mixed; a clean copper foil (15mm×15mm) was taken and the prepared silicon slurry was evenly coated on the copper foil with a thickness of about 95μm; the coated copper foil was placed in an oven and dried at 120°C for 2 hours to remove moisture and solidify the slurry on the copper foil to obtain a silicon-based negative electrode. Among them, the average particle size of the silicon nanoparticles is 80nm, and the coating amount of the negative electrode material layer is 2.0mg / cm 2 .

[0115] A button-type lithium-ion half-cell, the assembly method of which is as follows:

[0116] In a glove box, the silicon-based negative electrode sheet, lithium metal sheet and polypropylene separator were stacked to ensure the isolation of the two electrodes. 1M LiPF6 EC / DMC electrolyte (300 μL) was injected and packaged into a button cell under vacuum conditions.

[0117] Example 4

[0118] The preparation method of the conductive adhesive is basically the same as that of Example 1, except that the amount of PANi gel particles added is changed. Specifically, 10 mg of PANi gel particles are uniformly dispersed in 3 mL of PEDOT:PSS, and reacted at 90° C. for 10 h to obtain adhesive PEDOT / PANi.

[0119] A silicon-based lithium-ion battery negative electrode plate, the preparation method of which is basically the same as that of Example 1, except that the PEDOT / PANi conductive binder of this embodiment is used, and the coating amount of the negative electrode material layer is 1.75 mg / cm 2

[0120] A button-type lithium-ion half-cell, the assembly method of which is substantially the same as that of Example 1, except that the negative electrode plate of this embodiment is used.

[0121] Example 5

[0122] The preparation method of the conductive adhesive is basically the same as that of Example 1, except that the amount of PANi gel particles added is changed. Specifically, 15 mg of PANi gel particles are uniformly dispersed in 3 mL of PEDOT:PSS, and reacted at 90°C for 10 h to obtain an adhesive PEDOT / PANi conductive adhesive.

[0123] A silicon-based lithium-ion battery negative electrode plate, the preparation method of which is basically the same as that of Example 1, except that the PEDOT / PANi conductive binder of this embodiment is used, and the coating amount of the negative electrode material layer is 1.75 mg / cm 2

[0124] A button-type lithium-ion half-cell, the assembly method of which is substantially the same as that of Example 1, except that the negative electrode plate of this embodiment is used.

[0125] Example 6

[0126] The conductive adhesive is prepared in the same manner as in Example 4 to obtain adhesive PEDOT / PANi.

[0127] A silicon-based lithium-ion battery negative electrode plate, the preparation method of which is basically the same as that of Example 4, except that the ratio of PEDOT / PANi conductive binder to silicon nanoparticles is changed. The specific method is as follows:

[0128] The PEDOT / PANi conductive binder and silicon nanoparticles obtained above were stirred for 2 hours using a magnetic stirrer in a ratio of 2:8 to ensure that the silicon nanoparticles and the conductive binder were fully mixed; a clean copper foil (15 mm × 15 mm) was taken and the prepared silicon slurry was evenly coated on the copper foil with a thickness of about 65 μm; the coated copper foil was placed in an oven and dried at 120°C for 2 hours to remove moisture and solidify the slurry on the copper foil to obtain a silicon-based negative electrode sheet. The coating amount of the negative electrode material layer was 1.75 mg / cm 2 .

[0129] A button-type lithium-ion half-cell, the assembly method of which is basically the same as that of Example 4, except that the silicon-based negative electrode plate of this embodiment is used.

[0130] Example 7

[0131] The conductive adhesive is prepared in the same manner as in Example 4 to obtain adhesive PEDOT / PANi.

[0132] A silicon-based lithium-ion battery negative electrode sheet, the preparation method of which is basically the same as that of Example 4, except that the thickness of the negative electrode material layer is changed. In this embodiment, the thickness of the negative electrode material layer is 120 microns, and the coating amount is 2.35 mg / cm 2 .

[0133] A button-type lithium-ion half-cell, the assembly method of which is substantially the same as that of Example 4, except that the silicon-based negative electrode plate of this example is used.

[0134] Comparative Example 1

[0135] The preparation method of the conductive adhesive is basically the same as that of Example 4, except that (1) phytic acid is not added as a dopant in the preparation of polyaniline (PANi), but traditional hydrochloric acid is used. The specific method is as follows:

[0136] (1) Preparation of polyaniline (PANi)

[0137] 5 mmol of aniline was added into 2 mL of 1 mol / L hydrochloric acid aqueous solution, mixed evenly to obtain solution A, which was placed in a 4°C refrigerator for cooling; 1.25 mmol of ammonium persulfate was dissolved in 1 mL of deionized water to obtain solution B, which was placed in a 4°C refrigerator for cooling.

[0138] After solution A and solution B are cooled to 4°C, they are quickly mixed and gelation of the solution can be observed in a few minutes. They are placed in a 4°C refrigerator for 8 hours. After the polymerization reaction is complete, they are filtered and washed with ethanol to remove byproducts such as aniline oligomers. PANi gel particle powder is obtained by drying at room temperature with a particle size of 80-120nm.

[0139] (2) Preparation of poly (3,4-ethylenedioxythiophene)-polyaniline (PEDOT / PANi) conductive adhesive, the specific method is as follows:

[0140] 5 mg of PANi gel particles were evenly dispersed in 3 mL of PEDOT:PSS and reacted at 90°C for 10 h to obtain adhesive PEDOT / PANi.

[0141] A silicon-based lithium-ion battery negative electrode plate, the preparation method of which is as follows:

[0142] The obtained PEDOT / PANi conductive binder and silicon nanoparticles were mixed in a ratio of 1:9 using a magnetic stirrer for 2 hours to ensure that the silicon nanoparticles and the conductive binder were fully mixed; a clean copper foil (15mm×15mm) was taken and the prepared silicon slurry was evenly coated on the copper foil with a thickness of about 65μm; the coated copper foil was placed in an oven and dried at 120°C for 2 hours to remove moisture and solidify the slurry on the copper foil to obtain a silicon-based negative electrode. Among them, the average particle size of the silicon nanoparticles is 80nm, and the surface density of the negative electrode material layer is 1.75mg / cm 2 .

[0143] A button-type lithium-ion half-cell, the assembly method of which is as follows:

[0144] In a glove box, the silicon-based negative electrode sheet, lithium metal sheet and polypropylene separator were stacked to ensure the isolation of the two electrodes. 1M LiPF6 EC / DMC electrolyte (300 μL) was injected and packaged into a button cell under vacuum conditions.

[0145] Test example:

[0146] 1. Material performance characterization test

[0147] (1) Structural characterization

[0148] Figure 1 is a SEM photograph of the polyaniline gel particles prepared in Example 4. It can be explained that polyaniline (PANi) has a three-dimensional cross-linked network structure formed by dendritic nanofibers with a diameter of 60-100 nm.

[0149] Figure 2 1 and 1 are SEM photos of the PEDOT / PANi conductive adhesive prepared in Example 4 at different magnifications. It can be explained that the PEDOT / PANi conductive adhesive structure is composed of a three-dimensional porous network formed by interconnecting PEDOT sheets embedded with polyaniline gel particles.

[0150] (2) Material peeling test

[0151] Peel strength refers to the maximum force required to peel the materials together from the contact surface per unit width. The peeling angle is 180°, and the unit is (N / m), which reflects the bonding strength of the material.

[0152] The test method is: fixing the width and length of the negative electrode sheets prepared in the embodiment and the comparative example, using a tape of a certain specification, and using a universal tensile testing machine to test the peel strength of the negative electrode sheets.

[0153] 2. Battery electrochemical performance test:

[0154] At room temperature, the button cell was tested for cycle performance and rate performance using an electrochemical workstation. Voltage setting test parameters: the charge and discharge voltage range is 0.01V to 1.5V; the first cycle charge and discharge capacity and first coulomb efficiency are measured at a charge and discharge rate of 0.2A / g; 500 charge and discharge cycle tests are performed at a rate of 0.2A / g; and discharge tests at different rates are performed at rates of 0.2A / g, 0.4A / g, 0.8A / g, 1.6A / g, 3.2A / g and 0.1A / g.

[0155] The test results of the first coulombic efficiency, the first lithium desorption specific capacity and the lithium desorption specific capacity after 500 cycles of the batteries of the embodiment and the comparative example are shown in Table 1.

[0156] Table 1 Performance test of embodiments and comparative examples

[0157]

[0158] As shown in Table 1, the conductive adhesive prepared by the present invention and the corresponding battery have large peeling force and good adhesion, among which Example 4 has the best effect. At the same time, the first coulombic efficiency of the battery of the embodiment is significantly better than that of the comparative example. By optimizing the preparation process of the adhesive, the comprehensive performance of the battery obtained in Example 4 is significantly improved compared with the other embodiments and comparative examples.

[0159] Figure 3 The cycle life diagram and rate performance of the silicon-based negative electrode prepared with gel particles of different contents in Example 1 and Examples 4-5 of the present invention. Figure 3 , 5mgPANi, 10mgPANi, and 15mgPANi correspond to Example 1, Example 4, and Example 5, respectively. As can be seen from the figure, the gel particles prepared in Example 4 perform best in terms of cycle stability and rate performance. When the lithium insertion / extraction current density is 0.2A / g, the first coulombic efficiency is 88%, and the initial lithium desorption specific capacity is approximately 2107mAh / g. After 500 cycles, the lithium desorption specific capacity is still as high as 1092mAh / g. The battery prepared in the embodiment of the present invention not only has excellent low-rate cycle performance, but also after a series of different high and low current densities, the capacity is almost consistent with the initial low current density specific capacity, and the rate performance advantage is obvious.

[0160] Figure 4 The electrochemical performance diagrams of button-type lithium-ion half-cells with different active material mass ratios prepared from 10 mg of PANi gel particles of Examples 4 and 6 of the present invention. Figure 4In the figure, the active material ratio of 9:1 corresponds to Example 4; the active material ratio of 8:2 corresponds to Example 6 (the active material ratio refers to the ratio of silicon nanoparticles to PEDOT / PANi conductive binder). As can be seen from the figure, when the silicon nanoparticles and PEDOT / PANi conductive binder are in a ratio of 8:2, the first coulombic efficiency is 85% when the lithium insertion / extraction current density is 0.2A / g, and the initial lithium extraction specific capacity is about 2046.1mAh / g. In comparison, the silicon nanoparticles and PEDOT / PANi conductive binder in a ratio of 9:1 have a higher specific capacity and better cycle retention rate.

[0161] To solve the above problems, the present invention proposes a novel conductive adhesive based on poly (3,4-ethylenedioxythiophene) and phytic acid-doped polyaniline (PEDOT / PANi).

[0162] The binder of the present invention is prepared by a simple chemical synthesis method, avoiding the use of organic solvents, and significantly improving the mechanical stability of the PEDOT binder by means of the three-dimensional cross-linked network structure of phytic acid-doped polyaniline. At the same time, the conductive binder has a three-dimensional continuous conductive network structure, which can effectively alleviate the volume expansion problem of silicon-based negative electrode materials during the charging and discharging process, thereby significantly improving the cycle stability and capacity retention rate of the battery. The invention not only provides an efficient and environmentally friendly method for preparing a conductive binder, but also provides new ideas and solutions for the development of high-performance silicon-based lithium-ion batteries.

[0163] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.

Claims

1. A method for preparing a conductive adhesive, characterized in that: The preparation method comprises: uniformly dispersing conductive polymer gel particles in a polythiophene-polystyrene sulfonic acid mixture, reacting to obtain a polythiophene / conductive polymer composite, i.e., a conductive adhesive; The conductive polymer gel particles are obtained by mixing a conductive polymer with a phytic acid solution, adding ammonium persulfate, mixing, standing for reaction, and drying.

2. The preparation method according to claim 1, characterized in that: The preparation method of the conductive polymer gel particles comprises the following steps: S1: adding phytic acid solution to the conductive polymer and mixing them evenly to obtain a conductive polymer-phytic acid solution; S2: dissolving ammonium persulfate in water to obtain an ammonium persulfate solution; S3: cooling the conductive polymer-phytic acid solution and the ammonium persulfate solution, mixing them, standing them for reaction, filtering, washing, and drying them to obtain conductive polymer gel particles; In S1, the molar ratio of the conductive polymer to the phytic acid is 1-5:0.24-1.2; And / or, the mass concentration of the phytic acid solution is 20-50%; In S2, the concentration of the ammonium persulfate solution is 0.25 mmol / mL-1.25 mmol / mL; In S3, the molar ratio of the conductive polymer in the conductive polymer-phytic acid solution to the ammonium persulfate in the ammonium persulfate solution is 1-5:0.25-1.25; And / or, the cooling temperature is 1-4°C; And / or, the temperature of the static reaction is 1-4°C and the time is 8-24h.

3. The preparation method according to claim 1, characterized in that: The conductive polymer includes at least one of polyaniline and polypyrrole; And / or, the particle size of the conductive polymer gel particles is 60-100 nm; and / or, the mass volume ratio of the conductive polymer gel particles to the polythiophene in the polythiophene-polystyrene sulfonic acid mixture is 6-14 mg / mL: 1-4; And / or, the polythiophene comprises poly-3,4-ethylenedioxythiophene; And / or, in the preparation of the polythiophene / conductive polymer composite, the reaction temperature is 60-90° C. and the reaction time is 8-16 hours.

4. A conductive adhesive prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The viscosity of the conductive adhesive is 1000-5000 mPa.s.

5. A negative electrode material, characterized in that: The conductive adhesive comprises silicon nanomaterials, the conductive adhesive according to claim 4, or a conductive adhesive prepared by the preparation method according to any one of claims 1 to 3.

6. The negative electrode material according to claim 5, characterized in that The particle size of the silicon nanomaterial is 60-100 nm; And / or, in the negative electrode material, the mass ratio of the silicon nanomaterial to the conductive binder is 1-2:8-9; And / or, the negative electrode material is obtained by mixing and stirring the silicon nanomaterial and the conductive binder.

7. A negative electrode plate, characterized in that: It comprises a negative electrode current collector and a negative electrode material layer coated on at least one surface of the negative electrode current collector; the negative electrode material layer comprises the negative electrode material according to any one of claims 5-6.

8. The negative electrode sheet according to claim 7, characterized in that: The thickness of the negative electrode material layer is 50-150 μm; And / or, the coating amount of the negative electrode material is 1.5-2.0 mg / cm 2 .

9. The negative electrode sheet according to claim 7, characterized in that: The preparation method of the negative electrode plate is: coating the negative electrode material on at least one surface of a negative electrode current collector and drying the coating.

10. A battery, characterized in that: It comprises a positive electrode sheet, an electrolyte, and a negative electrode sheet as described in any one of claims 7 to 9.

Citation Information

Cited By

  • High-capacity lithium ion battery negative electrode material, preparation method thereof and lithium ion battery

    CN120511287A

  • Hole transport layer and flexible perovskite solar cell

    CN122206083A

  • A lithium ion battery anode based on a multifunctional conductive binder and a preparation method thereof

    CN122677443A